2020
DOI: 10.3390/biom10010118
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Direct Assay for Monitoring Fatty Acid Synthase Activity and Product-Specificity by High-Resolution Mass Spectrometry

Abstract: De novo fatty acid synthesis is a pivotal enzymatic process in all eukaryotic organisms. It is involved in the conversion of glucose and other nutrients to fatty acyl (FA) chains, that cells use as building blocks for membranes, energy storage, and signaling molecules. Central to this multistep enzymatic process is the cytosolic type I fatty acid synthase complex (FASN) which in mammals produces, according to biochemical textbooks, primarily non-esterified palmitic acid (NEFA 16:0). The activity of FASN is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…6C), suggests that the FASN is also critical to generating the CoA species used for these reactions. In support of this notion, two recent studies have found that FASN generates an array of fatty acyl chains than just 16:0 and that FASN supports the generation of myristoyl-CoA and stearoyl-CoA and their subsequent attachment to proteins (61,62). Does the loss of ZDHHC5 and FASN activity impact the SARS-CoV2 infection cycle by other mechanisms?…”
Section: Discussionmentioning
confidence: 94%
“…6C), suggests that the FASN is also critical to generating the CoA species used for these reactions. In support of this notion, two recent studies have found that FASN generates an array of fatty acyl chains than just 16:0 and that FASN supports the generation of myristoyl-CoA and stearoyl-CoA and their subsequent attachment to proteins (61,62). Does the loss of ZDHHC5 and FASN activity impact the SARS-CoV2 infection cycle by other mechanisms?…”
Section: Discussionmentioning
confidence: 94%
“…Recent advances in high-throughput MS resulted in highly sensitive and accurate methods for analyzing complex analytes, which have been especially useful for protein engineering applications. By utilizing native substrates and ligands, MS is capable of performing label-free high-throughput assays for characterizing complex mixtures of engineered proteins. However, no individual MS technique provides the ability to screen all proteins in a sample with enough information to characterize all possible modifications.…”
Section: Methodologiesmentioning
confidence: 99%
“…Furthermore, to directly test whether the FAS complex in fas2 3E cells produces a higher proportion of 18:0-CoA, we next carried out an in vitro assay to profile the FAS product specificity. To this end, we prepared cytosolic fractions containing the FAS complex and measured the incorporation of 13 C 3 -labeled malonyl-CoA into de-novo-synthesized FA chains (Topolska et al, 2020). Consistent with our results in vivo, the cytosol of fas2 3E cells produced a higher proportion of 13 C-labeled FA 18:0 (Figure 6F) and yielded a 1.6-fold increased ratio between C 18and C 16 -containing FA chains as compared to wild-type cells (D-F) Summary of lipid metabolic hallmarks of indicated mutant strains cultured in YPD (left panels) and examples of lipidome differences compared to wild type (right panels).…”
Section: Phosphorylation Of Cds1 and Cho1 Increases Enzymatic Activitymentioning
confidence: 99%
“…In vitro FAS activity analysis FAS activity was assayed using 13 C 3 -malonyl-CoA and high-resolution mass spectrometry as recently described (Topolska et al, 2020). In short, BY4742 and fas2 3E cells were grown to an OD 600 of $2.5 and 50 ODu of cells were harvested (3000 g, 3 min) and washed with sterile, deionized water.…”
Section: Flow Cytometrymentioning
confidence: 99%